Evaluating the perceptions and use of Computer Assisted Career Guidance Systems in seven high schools by learners and teachers: analysis, synthesis and computer effect - September, Unathi (School of Education, 2017)
Abstract This research is concerned with how learners perceive Computer Assisted Career Guidance Systems at schooling level in South Africa. The research is also about exploring how teachers in the high school setting use these Computer Assisted Career Guidance systems. The thesis defines Computer-Assisted Career Guidance Systems as "interactive guidance programs that an individual can operate independently to retrieve information useful for self-assessment and career exploration" (Fowkes & McWhirter, 2007, p. 388). The digital age has provided numerous Computer Assisted Career Guidance Systems (CACGS) platforms where information can be consumed and used to make career related decisions (Fowkes & McWhirter, 2007). However, the impact and effectiveness of these CACGS has not been investigated in the South African context, particularly the perceptions of learners and teachers at high school level. This may be due to few schools, often only private schools, in South Africa having the financial and human resources to use and interpret results of learners from these CACGS. In this thesis, four Computer Assisted Career Guidance Systems that are used in high schools were evaluated by learners, and these are PACE, Mindmuzik-EAS, The Online Career Guide and JVR Strong Interest Inventory. Furthermore, the thesis evaluated how teachers used these systems in class, the expectations by parents and how their respective schools evaluate the impact of CACGS against the school's objectives. The emergence and use of these CACGS in South African private schools provided an opportunity to research the perceptions of the impact that these technologies have on the decisions that high school leavers make. This study attempted to understand the usefulness of Computer Assisted Career Guidance Systems in high schools that have invested in these technologies. The research evaluated CACGS in seven schools with 177 learners participating and 7 school teachers/psychologists. Focusing specifically on three composite scales that measured whether learners believed that after using the CACGS they became familiar with oneself and the world of work (Analysis), if they believed that through CACGS they were able to identify potential career alternatives (Synthesis) and if they believed that interacting with the computer made a difference (Computer Effect). This thesis adopts a mixed method approach to study CACGS, using a qualitative method through interviews to get the opinion of teachers and a quantitative method through surveys to get learners' perceptions. This study afforded rare insight into the South African high schools use of CACGS, where findings indicated a general acceptance and satisfaction of CACGS from learners. Moreover, revealing how the systems are implemented in class.